1989
DOI: 10.1104/pp.90.3.792
|View full text |Cite
|
Sign up to set email alerts
|

cDNA Clones for Corn Leaf NADH:Nitrate Reductase and Chloroplast NAD(P)+:Glyceraldehyde-3-Phosphate Dehydrogenase

Abstract: cDNA clones were selected from a corn (Zea mays L.) leaf lambda gtl1 expression library using polyclonal antibodies for corn leaf NADH:nitrate reductase. One clone, Zmnrl, had a 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…Corn Nir was found to be encoded by a very different set of codons than the Nir gene of spinach (2,17). We found that corn Nar codon usage was narrowly biased as compared to a Nar gene of Arabidopsis (10,13). A recent study of 207 plant genes confirmed that codon usage in nuclear genes differed between monocots and dicots (22).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Corn Nir was found to be encoded by a very different set of codons than the Nir gene of spinach (2,17). We found that corn Nar codon usage was narrowly biased as compared to a Nar gene of Arabidopsis (10,13). A recent study of 207 plant genes confirmed that codon usage in nuclear genes differed between monocots and dicots (22).…”
mentioning
confidence: 64%
“…However, the high-level expression of the highly biased genes of monocots in the dicot system may be a problem. Genes such as Nar and Nir of corn as well as the corn chloroplastic Gap (8,13,17,28) may be very useful for experimentally testing the limits ofintergenic transfer in order to gain a better understanding ofbiased codon usage in higher plants.…”
Section: Significance Of Biased Codon Usage In Higher Plantsmentioning
confidence: 99%
“…Flavodoxin reductase arginine residues 144, 174 and 184 are highlighted in bold, as are positively charged amino acids (arginines and lysines) conserved in the aligned enzymes. Spinach, spinach FNR (Swiss-Prot code P00455, [24]) ; Anabaena, ferredoxin reductase from Anabaena variabilis (Q4459) ; P450 BM3, flavocytochrome P450 BM3 from Bacillus megaterium (P14779, [25]) ; Hum CPR, human NADPH-cytochrome P450 reductase (P16435, [26]) ; Rat CPR, rat NADPH-cytochrome P450 reductase (P00388, [27]) ; B5 R 'ASE, bovine NADH-cytochrome b 5 reductase (P07514, [28]) ; Hum iNOS, human inducible nitric oxide synthase (NOS ; P35228, [29]) ; Hum nNOS, human neuronal NOS (P29475, [30]) ; Hum eNOS, human endothelial NOS (P29474, [31]) ; Corn NIR, corn nitrate reductase (P17571, [32]). Bovine cytochrome b 5 reductase and corn nitrate reductase are NADH-dependent reductases, all other enzymes shown are NADPH-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was fractionated (10 rglsample) in formaldehyde-agarose denaturing gels by electrophoresis and transferred to nitrocellulose. Maize NR mRNA levels were probed by hybridization with a 32P-labeled cDNA clone of the maize NR mRNA (Gowri and Campbell, 1989) as previously described (Redinbaugh et al, 1988;Gowri et al, 1992). Briefly, a nonspecifically bound probe was eliminated by washing the membrane in 0.1 X SSC (0.15 m~ Na-citrate, pH 7.0, 15 m~ NaC1, 0.1% [w/v] SDS) at 65OC for at least 1 h. The Zmnrl cDNA hybridized with an mRNA of about 3.2 kb as previously seen (Gowri and Campbell, 1989).…”
Section: Rna Isolation and Northern Blot Analysis Of Nr Rnrnamentioning
confidence: 99%